Factors correlated with internet gaming disorder among Malaysian university students - Nik Jaafar, Nik Ruzyanei; Baharuddin, Azlin; Tajjudin, Izzat; Ling, Ling Shiao; Safarudin, Muhammad Amirul; Don Shakir, Sufia; Hui, Tan Ying; Zulkifle, Nur Hasya; Tan, Kit Aun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Internet gaming disorder (IGD) has recently been incorporated into the Diagnostic and Statistical Manual of Mental Disorders fifth edition (DSM-5) as a disorder for future research. The primary objectives of the present study are to describe the level of IGD and to examine its correlations with sociodemographic factors and psychological comorbidities among undergraduate students in a Malaysian university. Methods: A total of 411 undergraduate students completed an online questionnaire. They were selected from a random sample of participating university faculties. The online questionnaire contained the Internet Gaming Disorder Scale-Short-Form and the Depression, Anxiety, Stress Scale. Results: The presents study reported that 52.8% of the participants had high IGH. Using hierarchical multiple regression, age (β = -0.09, p < 0.05), gender (β = -0.40, p < 0.001) and stress (β = 0.23, p < 0.05) were statistically significant predictors of IGD. Academic performance, depression and anxiety did not emerge as significant predictors. Conclusion: These findings highlight the risk factors (in particular, stress) of IGD. Further studies on interventions, particular that of preventative strategies, will be needed to combat this emerging public health problem.